Tindak Tutur Lokusi di Kanal YouTube Arisa Nur Aini - Ismi Aulia Sari; Shinta Anggraeni Setyowati; Marchell Teja Kusuma; Setiya Adi Buono; Asep Purwo Yudi Utomo (Universitas Indraprasta PGRI, 2023)
Locution is a speech act that exists in pragmatic studies, locution itself can be interpreted as a speech act that states something where the action produces a meaningful expression. The other name of this speech act is the act of saying something. In everyday life, we definitely find locutionary speech acts, one of which is in the form of Indonesian language learning videos on YouTube. Therefore, researchers want to examine more deeply about the locutionary speech act. This research is focused on one of the fields of pragmatics, namely speech acts. The analysis was conducted on learning videos on Arisa Nur Aini's YouTube channel, namely on the playlist of Indonesian Language Materials for Grade 11 SMA semester 1 which was motivated by the discovery of the use of various types of locutionary speech acts in the sentence. The data source used is the Indonesian learning video of Grade 11 Material. The data used is in the form of utterances in the learning video which are included in the type of locutionary speech acts. The research method used in this research is a qualitative descriptive method which uses data collection techniques in the form of listening and recording techniques. The purpose of this study is to determine the types of locutionary speech acts in playlists of Indonesian Language Materials for Grade 11 SMA semester 1 on Arisa Nur Aini's youtube channel. From the analysis, it is found that the types of locutionary speech acts in the form of interrogative sentences consisting of 7 utterances, declarative sentences consisting of 20 utterances, and imperative locutionary speech acts consisting of 7 utterances. With this analysis, the readers are expected to be able to interpret and classify the types of locutionary speech acts. Keywords: lokusi, pragmatic, arisa, youtube, sma